Inconclusive evidence for causal effects between rumination and sleep problems: a simulated reanalysis and comment on Yang and Lei (2025) - Sorjonen, Kimmo; Melin, Bo (Frontiers in Psychology, 2025)
BackgroundBased on findings from analyses with cross-lagged panel models, Yang and Lei suggested reciprocal causal effects between rumination and sleep problems. However, it is well known that findings from cross-lagged panel models may be spurious.MethodWe simulated data to resemble the data used by Yang and Lei. We used triangulation and fitted complementary models to the simulated data.ResultsWe found contradicting increasing and decreasing effects of initial rumination on subsequent change in sleep problems and vice versa.ConclusionThe divergent findings indicated that it is premature to assume causal effects between rumination and sleep problems and the suggestions by Yang and Lei in this regard can be challenged. It is important for researchers to be aware that correlations, including adjusted cross-lagged effects, do not prove causality in order not to overinterpret findings, something that appears to have happened to Yang and Lei. We recommend researchers to triangulate by fitting complementary models to their data in order to evaluate if analyzed data could be used to support contradicting conclusions, in which case the data should not be used to support any of those conclusions.